Mouse Hepatitis Coronavirus RNA Replication Depends on GBF1-Mediated ARF1 Activation - Verheije, Monique H.; Raaben, Matthijs; Mari, Muriel; te Lintelo, Eddie G.; Reggiori, Fulvio; van Kuppeveld, Frank J. M.; Rottier, Peter J. M.; de Haan, Cornelis A. M. (PLoS pathogens, 2008)
Coronaviruses induce in infected cells the formation of double membrane vesicles, which are the sites of RNA replication. Not much is known about the formation of these vesicles, although recent observations indicate an important role for the endoplasmic reticulum in the formation of the mouse hepatitis coronavirus (MHV) replication complexes (RCs). We now show that MHV replication is sensitive to brefeldin A (BFA). Consistently, expression of a dominant-negative mutant of ARF1, known to mimic the action of the drug, inhibited MHV infection profoundly. Immunofluorescence analysis and quantitative electron microscopy demonstrated that BFA did not block the formation of RCs per se, but rather reduced their number. MHV RNA replication was not sensitive to BFA in MDCK cells, which are known to express the BFA-resistant guanine nucleotide exchange factor GBF1. Accordingly, individual knockdown of the Golgi-resident targets of BFA by transfection of small interfering RNAs (siRNAs) showed that GBF1, but not BIG1 or BIG2, was critically involved in MHV RNA replication. ARF1, the cellular effector of GBF1, also appeared to be involved in MHV replication, as siRNAs targeting this small GTPase inhibited MHV infection significantly. Collectively, our results demonstrate that GBF1-mediated ARF1 activation is required for efficient MHV RNA replication and reveal that the early secretory pathway and MHV replication complex formation are closely connected.